Towards Sustainable Circular EV Battery Value Chains: A Review and Comparative Analysis Between Germany, Norway, and Japan - Kishita, Yusuke; Boks, Casper; Proff, Moritz; Uhlig, Edith; Ahmed, Saad; Pantelatos, Leander; Mennenga, Mark; Blomeke, Steffen; Scheller, Christian; Amasawa, Eri; Grimmel, Philipp (2024 Electronics Goes Green 2024+ (EGG), 2024)
In response to increased momentum towards a circular economy, much attention has been paid to circular battery businesses to create economic values from used batteries collected from electric vehicles (EVs) and to mitigate supply chain risks of battery materials. Numerous practices of circular battery businesses are found around the world, such as refurbishment, repurposing, and recycling, but most of them are still at a small scale. In this research, we provide a review and comparative analysis of the state-of-the-art circular battery business development in three countries, namely Germany, Norway, and Japan. We focus on lithium-ion batteries (LiBs) as they are most prevalent in the EV market. Based on a cross-country comparison, key enablers and inhibitors to design economically and environmentally sustainable LiB circular systems are discussed, and future research directions are proposed.